Complete genome sequence of a novel cytorhabdovirus infecting elderberry (Sambucus nigra L.) in the Czech Republic - Šafářová, Dana; Candresse, Thierry; Navrátil, Milan (Archives of virology, 2022)
The genus Cytorhabdovirus includes plant viruses with an unsegmented, single-stranded, negative-sense RNA genome that infect various plant hosts. In this work, we report the detection of a new cytorhabdovirus infecting elderberry (Sambucus nigra L.). Total RNA was purified from infected leaves and, after ribodepletion, sequenced using an Illumina system. The RNA genome of viral isolate B15 is 12,622 nucleotides (nt) long, and that of isolate B42 is 12,621 nt long. A nearly complete sequence (12,592 nt) was also obtained for a third isolate (B160). The RNA genomes of all three isolates showed an organisation typical of cytorhabdoviruses, harbouring all six of the expected genes (3´ N-P-P3-M-G-L 5´), separated by intergenic regions. These isolates were closely related to each other (99.5-99.6% nt sequence identity) and showed the highest overall similarity to trichosanthes associated rhabdovirus 1 (63.5% identity) and Wuhan insect virus 5 (58% identity), and similar results were obtained when comparing individual coding sequences or proteins. Phylogenetic analysis confirmed that this elderberry virus, for which we propose the name "sambucus virus 1" belongs to the genus Cytorhabdovirus and fulfils the criteria to represent a novel species.
Keywords: bez; Sambucus; Sambucus nigra; genom virový; Rhabdoviridae; bez černý; Open Reading Frames; otevřené čtecí rámce; virové proteiny; Česká republika; Genome, Viral; Phylogeny; RNA; Viral Proteins; fylogeneze; nemoci rostlin; Czech Republic; Plant Diseases